2007
DOI: 10.1007/s10658-007-9141-9
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to infection by stealth: Brassica napus (winter oilseed rape) and Pyrenopeziza brassicae (light leaf spot)

Abstract: Light leaf spot (Pyrenopeziza brassicae)is an important disease on winter oilseed rape crops (Brassica napus) in northern Europe. In regions where economically damaging epidemics occur, resistance to P. brassicae in commercial cultivars is generally insufficient to control the disease without the use of fungicides. Two major genes for resistance have been identified in seedling experiments, which may operate by decreasing colonisation of B. napus leaf tissues and P. brassicae sporulation. Much of the resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 53 publications
1
46
0
Order By: Relevance
“…They then colonise the subcuticular niche, where extensive hyphal networks can be observed microscopically (Fig. 1b), although there are few visual symptoms on leaves of crops during this endophytic, apoplastic phase in the epidemic cycle (Rawlinson et al 1978b;Boys et al 2007Boys et al , 2012. Early infections during autumn and winter can kill seedlings, decrease plant vigour and increase susceptibility to frost damage (Fitt et al 1998b).…”
Section: Light Leaf Spot Epidemiologymentioning
confidence: 99%
See 4 more Smart Citations
“…They then colonise the subcuticular niche, where extensive hyphal networks can be observed microscopically (Fig. 1b), although there are few visual symptoms on leaves of crops during this endophytic, apoplastic phase in the epidemic cycle (Rawlinson et al 1978b;Boys et al 2007Boys et al , 2012. Early infections during autumn and winter can kill seedlings, decrease plant vigour and increase susceptibility to frost damage (Fitt et al 1998b).…”
Section: Light Leaf Spot Epidemiologymentioning
confidence: 99%
“…The asymptomatic growth phase of the pathogen starts with the formation of a hypomycelium, followed by proliferation of fungal hyphae to produce mycelial plates within the subcuticular space (Rawlinson et al 1978b). Prior to and during this stage, twoway communication occurs between the pathogen and the host plant in which the pathogen attempts to utilise the host metabolism for its growth and reproduction, whereas the host may defend itself against the pathogen after recognition of pathogen signals (Boys et al 2007). It has been shown that extracellular cutinases (Pbc1) (Li et al 2003), extracellular proteases (Psp1) (Batish et al 2003) and cytokinins (Ashby 1997) are key pathogenicity determinants involved during the penetration and subcuticular growth of the pathogen.…”
Section: Pathogenicity Determinantsmentioning
confidence: 99%
See 3 more Smart Citations